INFLUENTIAL FACTORS ON SMES INTENTION TO EXPORT FROM THE PERSPECTIVE OF INNOVATION DIFFUSION - Yogi Yusuf Wibisono (International Journal of Economics, Business and Accounting Research (IJEBAR), 2023)
A country's export level contributes greatly to its economy. Despite accounting for 99% of all companies, the contribution of small and medium-sized enterprises (SMEs) to national export in Indonesia is quite low, at 15.6%. The relatively low contribution of SMEs to export encourages scholars to look at the factors that impact or discourage SMEs from exporting their products. This study aims to build a model of internationalization adoption, i.e. export to foreign markets, based on the concept of innovation diffusion, with five dimensions: relative benefits, compatibility, complexity, trialability, and observability, in order to gain a better understanding of how internationalization as an innovation spreads in SMEs. The survey approach is employed, with questionnaires sent to SMEs in Bandung, and the data obtained is used to evaluate the model. According to the findings of the data analysis, relative benefits complexity, trialability, and observability all have a substantial impact on SMEs' intentions to export.